Tinjauan Kritis tentang Program Tayangan Anak di Televisi - Fardiah, Dedeh (Mediator, 2006)
In the field of mass communication, studies concerning children and mass media always provide interesting perspectives, especially concerning the effect of television viewing . Each year, communication experts, psychologists, as well as parents attended this issue seriously. From communication and psychological perspectives, televisions were blamed as the source of the problem due to bad program qualities as well as high frequent of TV  violence, and sexual content. Employing Critical Theories for analyzing device, this article addresses the map of children program on TV, and how the program was packed. Children program on TV still face many obstacles, including the challenge thrown by rating on media market industries.